Evaluation of the implementation of interactive video-based online learning in practical courses using the CIPP model - Sudaryono Sudaryono (Graduate School, Universitas Negeri Yogyakarta, 2021)
This study aims to examine the evaluation of the implementation of interactive video-based online learning for the 2020/2021 academic year at Raharja University, Tangerang City, Banten. The research design uses a quantitative approach. Techniques Data collection is done through questionnaires, interviews, and documentation studies. The item instrument validation was carried out using the validity and reliability test of the data with consistent results (0.8800.60). The study involved 103 participants employing a descriptive data analysis technique using the CIPP evaluation model. The findings show that the average score for all aspects is 80.55%, in the very good category. First, the implementation of learning is in accordance with the Central and Regional Government Regulations and the Learning from Home Guide for the Even Semester of the 2020/2021 Academic Year. Second, input in the implementation of online learning based on video learning in accordance with the planning criteria in the implementation of practical courses. Third, the Learning Implementation Process is an alternative method used by lecturers to overcome online learning obstacles. Fourth, the Learning Products have met the policy standards of educational institutions. It is hoped that the implementation of interactive video-based online learning on educational sites can be continuously improved by evaluating the implementation of learning to achieve much better learning performance and a higher level of student satisfaction than those who do not use it.